Database Click Stream of E-commerce Functional - Evi Triandini; I Gede Suardika; I Ketut Putu Suniantara (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2021)
The availability of e-commerce functionality that suits for user needs in e-commerce applications will increase the sustainability of application usage and can provide benefits for its users. Many e-commerce applications have been developed, but based on the results of previous research, these e-commerce applications do not pay attention to the availability of functionality and its advantages in the application. A database design to store functional clickstream ecommerce is required to determine the number of features that users are accessing. Database application development is the activity of identifying real-world requirements, analyzing requirements, designing system data and functions, and then implementing operations in the system. The database life cycle method is used to build a database in this study. This research has produced a click stream database that has added functional attributes available in e-commerce, which are accessed by users. The results also show the addition of several tables that will facilitate the management of click stream data functionality from e-commerce applications.